Role of technetium scan in diagnosis of congenital hypothyroidism - N., Prasad Nayak; Maben, Roshan; Chako, Nisha; Soans, Santosh T. (International Journal of Research in Medical Sciences, 2017)
Background: With advent of screening new born population the incidence of congenital hypothyroidism dropped to 1:3000 to 1:4000. We have aimed to show the importance of doing technetium scan to find out exact etiology of congenital hypothyroidism. It helps in proper treatment and explaining the long-term prognosis. However, many centres in India do not have facilities for nuclear study. Methods: Study comprised of 30 children, the results of thyroid function test (TFT) were analysed, ultrasound neck was done to detect the presence or absence of thyroid gland in the neck and technetium scan was done in the department of nuclear medicine. Based on the images its classified as agenesis, ectopic or decreased uptake. The results of TFT, Ultrasound neck, technetium scan was analysed using statistical software. Results: Correlation of thyroid profile with technetium scans, T3 was decreased in 61.5% cases of ectopic thyroid, 100% cases of thyroid agenesis and 83.3% cases of decreased uptake. T4 was decreased in 92.3% cases of ectopic thyroid, 80% cases of thyroid agenesis and 75% of decreased uptake. Whereas TSH increased in all the cases with abnormal Technetium scan results. Correlation of ultrasound neck with technetium scans revealed, of the nonvisualised thyroid gland by ultrasound, 13 were ectopic, 5 agenesis and 5decreased uptake. of the visualized thyroid gland, all the 07 showed decreased uptake. Conclusions: Congenital hypothyroidism is one of the most serious condition needs to be diagnosed as early as in the newborn period.